2021
DOI: 10.1155/2021/6694150
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Intravenous Nitroglycerin Bolus Doses in Reducing Hemodynamic Responses to Laryngoscopy and Endotracheal Intubation

Abstract: Background. Hemodynamic responses to laryngoscopy and endotracheal intubation are transient in most patients. However, in some patients with a history of heart disease, systemic hypertension, or cerebrovascular disease, these may lead to dangerous complications. This study is aimed at determining the effectiveness of intravenous nitroglycerin bolus doses in reducing hemodynamic responses to laryngoscopy and endotracheal intubation. Material and Method. In this double-blind randomized controlled trial, 78 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The endotracheal intubation procedure can lead to sympathetic nervous system activation that causes an unstable hemodynamic response ( 24 ). In most patients, these hemodynamic responses are transient; however, in patients with cardiovascular and/or cerebrovascular diseases, these responses might produce dangerous complications ( 25 ). Patients undergoing suspension laryngoscopic surgery encounter the same cardiac reaction secondary to the sympathetic reflex and release of catecholamines, even though the stimulation is much more intensive and is sustained much longer than the transient process of endotracheal intubation ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…The endotracheal intubation procedure can lead to sympathetic nervous system activation that causes an unstable hemodynamic response ( 24 ). In most patients, these hemodynamic responses are transient; however, in patients with cardiovascular and/or cerebrovascular diseases, these responses might produce dangerous complications ( 25 ). Patients undergoing suspension laryngoscopic surgery encounter the same cardiac reaction secondary to the sympathetic reflex and release of catecholamines, even though the stimulation is much more intensive and is sustained much longer than the transient process of endotracheal intubation ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hajian et al . [ 13 ] studied the effect of bolus doses of 1 μg/kg and 2 μg/kg IV nitroglycerine to reduce haemodynamic responses to laryngoscopy and intubation. They observed that the most marked blood pressure decrease from the baseline was seen in the group receiving 2 μg/kg dose of nitroglycerine without much of a difference in HR between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Laryngoscopy and endotracheal intubation elicit profound hemodynamic changes characterized by increased heart rate and blood pressure. These responses can be particularly detrimental in individuals with limited cardiorespiratory reserve (1), highlighting the importance of attenuating sympathetic stimulation (2).…”
Section: Introductionmentioning
confidence: 99%